HUBUNGAN RIWAYAT HIPERTENSI SELAMA KEHAMILAN, INDEKS MASA TUBUH DAN POLA MAKAN DENGAN HIPERTENSI PADA KEHAMILAN DI PUSKESMAS PEDAMARAN TIMUR TAHUN 2020: Yusra Agustini, Sendy Pratiwi Rahmadhani, Sri Handayani - Yusra Agustini (Biro Riset, Inovasi dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2020)
Pregnancy hypertension is one of the causes of illness and death worldwide for both mother and fetus. Globally, 80 percent of maternal deaths are classified as direct causes of maternal death. This study aims to determine the relationship between history of hypertension, body mass index, diet and the incidence of hypertension in pregnancy at Puskesmas Pedamaran Timur in 2020. This type of research uses quantitative methods. The population of this study were pregnant women at Puskesmas Pedamaran Timur from January to June 2020. Samples were taken using non-random sampling with accidental sampling technique. Data collection techniques are carried out through medical records, questionnaires and interviews. The results showed that of the 94 respondents studied, the proportion of mothers suffering from hypertension during pregnancy was 20.2%. 10.6% of mothers who had a history of hypertension during pregnancy. Mothers whose body mass index was as much as 74.5%. The proportion of mothers with a good diet was 47.9%. The results of the analysis using the Chi-Square statistical test with a significance limit of ? = 0.05 in the history of hypertension during pregnancy with the incidence of hypertension in pregnancy obtained p value = 0.000? ? = 0.05. In the diet with the incidence of hypertension in pregnancy, the p value = 0.002 <? = 0.05. In the diet with the incidence of hypertension in pregnancy, the p value = 0.001 <? = 0.05. So it can be concluded that there is a relationship between history of hypertension during pregnancy, between body mass index, diet and the incidence of hypertension in pregnancy.